Stem Cells : A Very Short Introduction - Slack, Jonathan (Oxford, New York Oxford University Press, 2016)
The topic of stem cells has been very high profile in the media in recent years. There is much public interest in stem cells but also much confusion and misinformation, with some companies already offering 'stem cell products' and bogus 'stem cell therapies'. In this Very Short Other, Jonathan Slack introduces stem cells; what they are, what scientists do with them, what stem cell therapies are available today, and how they might be used in future. Despite important advances, clinical applications of stem cells are still in their infancy. Most real stem cell therapy today is some form of bone m.
Include Illustration, Glossary and Index
Keywords: Stem cells